13.7k views
5 votes
Solve for k.
k² - 19k - 20 =0

User Ezran
by
5.6k points

2 Answers

4 votes

Answer:

k² - 19k - 20

(k-20) (k+1) = 0

k-20 = 0

k=20

k+1 = 0

k= -1

k= 20 and -1

Solve for k. k² - 19k - 20 =0-example-1
User Wczekalski
by
4.8k points
3 votes

Answer:

k = -1, 20

Explanation:

k² - 19k - 20 = 0

k² + 1k - 20k - 20 = 0 ==> 1 * (-20) = -20 and -20 + 1 = -19

k² + k - 20k - 20 = 0

k(k+1) - 20(k+1) = 0 ==> factor and simplify

(k-20)(k+1) = 0

k-20=0 ==> k=20

k+1=0 ==> k=-1

k = -1, 20

User Paul Du Bois
by
5.5k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.